Pengaruh Bantuan Luar Negeri Terhadap Pertumbuhan Ekonomi Negara ASEAN - Dheylla Permatasari Depinto; Melti Roza Adry; Hari Setia Putra (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to determine the effect of several macroeconomic variables on the economic growth of ASEAN countries. The variables used in this study are foreign aid, foreign direct investment, inflation, and economic growth. This study uses Panel Regression Analysis to see the effect of the independent variables on the dependent variable which can be seen from the annual data from 2009 to 2019 collected through documentation from related agencies and internet websites. The results of this study show that: (1) Foreign Direct Investment has a positive and insignificant effect on the economic growth of ASEAN countries. (2) Inflation has a positive and significant impact on the economic growth of ASEAN countries. (3) Foreign Aid has a negative and insignificant effect on the economic growth of ASEAN countries.